2009
DOI: 10.1183/09031936.00117708
|View full text |Cite
|
Sign up to set email alerts
|

Asthma, airway inflammation and epithelial damage in swimmers and cold-air athletes

Abstract: Endurance athletes show an increased prevalence of airway hyperresponsiveness. The aim of the present study was to evaluate the long-term effects of training on airway responsiveness, inflammation and epithelial damage in swimmers and cold-air athletes.In total, 64 elite athletes (32 swimmers and 32 cold-air athletes), 32 mild asthmatic subjects and 32 healthy controls underwent allergy skin prick testing, methacholine challenge and induced sputum analysis.Overall, 69% of swimmers and 28% of cold-air athletes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
138
2
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(159 citation statements)
references
References 36 publications
11
138
2
7
Order By: Relevance
“…That observation gives support to our results and to the concept of non-sensitising asthma from low level exposure to irritating agents such as dust, fumes and vapour. Interestingly, outside working life, athletes such as swimmers who are exposed to chlorine and cross-country skiers inhaling cold air are observed as having an increased incidence for asthma (Bougault et al 2009). Again, the exposure of these groups of athletes seems to be non-sensitising.…”
Section: Discussionmentioning
confidence: 99%
“…That observation gives support to our results and to the concept of non-sensitising asthma from low level exposure to irritating agents such as dust, fumes and vapour. Interestingly, outside working life, athletes such as swimmers who are exposed to chlorine and cross-country skiers inhaling cold air are observed as having an increased incidence for asthma (Bougault et al 2009). Again, the exposure of these groups of athletes seems to be non-sensitising.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the long-term inhalation of cool air is associated with the induction of lung injury and airway remodeling in endurance athletes. Winter sports athletes spend many hours per week training in cold and dry air, and it has been observed that they particularly display respiratory symptoms and airway hyper responsiveness (Bougault et al, 2009;Karjalainen et al, 2000;Sue-Chu et al, 1999). Additional studies on temperature fluctuations during hibernation in lung are absent; hence, we investigated changes in lung histology in the hibernating Syrian hamsters.…”
Section: Introductionmentioning
confidence: 99%
“…Some competitive swimmers develop VCD [59]. Children and adolescents who repeatedly swam, and were exposed to chlorine additives for water disinfection, could become symptomatic [75,[77][78][79][80][81][82]. Apparently, chlorine dissolved in swimming pool water would not pose a danger for the majority of swimmers.…”
Section: Discussionmentioning
confidence: 99%